Bamboo Utilization in Southern India - Vijendra Rao, R.; Gairola, S. C.; Shashikala, S.; Sethy, A. K. (Indian Forester, 2008)
Bamboo occupies a prominent place in the socio-economic and cultural life of Indians. It has been a source of number of uses since ancient times. India is the second largest in bamboo production with the highest growing stock concentrated in the North-East states. This paper outlines the consumption pattern of different species of bamboo in various sectors like agriculture, aquatic environment, socio-religious functions, sericulture, agarbathi industry and furniture. It also emphasizes the importance of research on bamboo improvement programme to produce better quality material in terms of physico-mechanical properties and the role of training in efficient utilization of this unique raw material.